Thermal Analysis of a Forced Flow Diffusion Absorption Refrigeration System for Fishing-Boat Exhaust Waste Heat Utilization - Du, Shuai (Frontiers in Energy Research, 2021)
Ammonia water absorption refrigeration systems are effective in utilizing fishing-boat exhaust waste heat for cryopreservation. However, the liquid level control and the use of a solution pump characterized by small flowrate and high-pressure head result in poor reliability in the traditional system. Besides, the system must necessarily be designed anti-swaying and anti-corrosion. This paper proposes a forced flow diffusion absorption refrigeration system, in which an inherently leak-free canned motor pump and an ejector are employed to provide the driving forces of the gas and liquid loops. The approximate single pressure operation allows for a simple passive liquid sealing control without throttling valves. The system adopts an integrated cooling strategy which allows the system to operate under swaying conditions, and the external seawater cooled heat exchanger avoids internal corrosion and leakage. The thermal analysis shows the system is valid to be operated under wide operating conditions, and the coupled gas and solution circulation ratios determined the performance of the novel system. There is an optimal ammonia mass fraction difference in the gas loop to obtain the optimal COP. The COP reaches 0.4 when the temperatures at the outlets of the generator, evaporator, absorber, and condenser are 160, −15, 35, and 35°C, respectively. The novel system provides a reliable absorption refrigeration system design for fishing-boat applications.